البعاد التربويّة القرآنية ف مواجهة الابئة االمراض - Asma’ Alahmad; Haziyah Hussin (Penerbit Universiti Kebangsaan Malaysia, 2022)
The pandemic of epidemics and diseases such as Coronavirus 19 that the world has gone through has greatly impacted people's lives psychologically, economically, socially, educationally, and faithfully. They desperately needed effective treatments to help them cope with the afflictions they were going through in their lives. In the Quran, many verses can inculcate patience and perseverance in the individual during difficulties, especially those related to paradise. This research aims to study the verses of paradise in the Holy Quran analytically and to extract the educational dimensions of these verses that have an important impact in the face of adversity and hardship. This study uses the thematic interpretation approach by filtering out verses about paradise in the Quran, which address the same topics and goals related to hardship, and then interpreting them with other verses of the Quran that address the same subject, also using the hadiths of the Prophet PBUH, and the views of Salaf al-Salih. The analytical approach was used to come up with the effects of faith from the educational dimensions that impact the Muslim’s life. The research found four educational guidelines that have an important impact in confronting epidemics and diseases: patience for affliction, integrity, and tranquillity, compassion and good deeds, and spending for the sake of God. It can strengthen the believer the faith in God Almighty and positive dealing in the face of afflictions, especially in this pandemic that has afflicted the whole world.